Harry Potter and the prisoner of Azkaban - Rowling, J. K. (London, Bloomsbury publishing Plc, 1999)
When Harry and his best friends go back for their third year at Hogwarts, the atmosphere is tense. There's an escaped mass-murderer on the loose and the sinister prison guards of Azkaban have been called in to guard the school.
Keywords: English fiction